The Influence of Digital Advertising Interactivity on Generation Z's Purchasing Intensity in the Fashion and Beauty Industry - Erick Lauren Ray; Franky Okto Bernando; Bayu Giri Prakosa (International Journal of Applied Business and International Management, 2026)
The rapid growth of digital marketing has increased the importance of interactive advertising in influencing consumer behavior, particularly among Generation Z consumers in the fashion and beauty industry. This study aims to analyze the influence of digital advertising interactivity on purchase intensity, with attitude toward digital advertising serving as a mediating variable. This study employed a quantitative approach using data collected from 312 Generation Z respondents who actively use social media platforms and are frequently exposed to digital advertising. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital advertising interactivity has a positive and significant effect on attitude toward digital advertising (beta = 0.68; p 0.001) and purchase intensity (beta = 0.21; p = 0.002). In addition, attitude toward digital advertising significantly affects purchase intensity (beta = 0.54; p 0.001) and partially mediates the relationship between digital advertising interactivity and purchase intensity (beta = 0.37; p 0.001; VAF = 63.8%). The study concludes that interactive digital advertising strategies play an important role in enhancing consumer engagement and encouraging purchasing behavior among Generation Z consumers in the fashion and beauty industry.